The role of public service bargains in cutback management: Insights in reforms in the Dutch penitentiary sector. (January 2021) - Schmidt, Eduard
Public managers need to interact with their political principals when managing cutbacks. However, research on cutback management did not put much emphasis on this interaction. We analyse how the interaction between public managers and political principals develops during cutbacks, and how this affects cutback management. We analyse these interactions between political principals and public managers as a public service bargain. This study employs an in-depth qualitative case study on recent cutbacks in the Dutch penitentiary system. The results show that cutbacks put the interaction between public managers and political principals under pressure. As political principals feel that public managers' loyalty towards them is violated, they centralise decision making. Consequently, public managers are withheld responsibility for cutback management. Strong resistance to cutbacks from public managers and subsequent political uproar leads to both actors having to find a new balance in the bargain. Furthermore, it leads to changes in both the content (what is cut back back) and the process (how are cutbacks decided upon and implemented) of cutback management. The first conclusion of this study and our contribution to the cutback management literature is that if we want to understand the work and behaviour of public managers during cutbacks, we cannot neglect the political context public managers work in. Second, we contribute to the literature on PSBs, as we conclude that cutbacks, even if they do not impact the institutional, formal part of the bargain, have the potential to affect public service bargains and thus, the interactions between public managers and political principals.